Análise Sedimentar e Micropaleontológica (Foraminíferos) de Seções Quaternárias do Talude Continental Superior do Norte da Bahia, Brasil - ARAÚJO, TÂNIA MARIA FONSECA; MACHADO, ALTAIR DE JESUS (Pesquisas em Geociências, 2008)
Sediment from four cores of the north part of the continental upper slope, Bahia State, consist predominantly of siliciclastic mud in its bottom and carbonatic mud in the top of the majority of the studied cores. The sediment color varies from light olive gray to brownish black. The sediments are mainly composed of foraminifera, mollusk fragments, coralline algae debris, plant fragments and quartz grains. The following major foraminifera benthonic species were recorded in the studied cores: Cibicides pseudoungerianus, Bulimina marginata, Amphistegina lessonii, Cassidulina laevigata, Bolivina subaenariensis, Uvigerina peregrina. The following major foraminifera planctonic species are frequent in the cores: Globigerinoides ruber, Globigerina bulloides, Orbulina universa, Globigerinoides trilobus, G. elongatus, Globigerina quinqueloba, Globigerinoides ruber f. pyramidalis. The siliciclastic sediment (higher quartz percentage) in the core bottom, suggests that sedimentation occurred with strong continental influence, indicating proximity to the coast line. The benthonic foraminifera predominance in the bottom cores and the higher planctonic frequency toward the top cores is an indicative of the sea-level oscilation events during Quaternary time.